Tinjauan Etika Bisnis Islam Terhadap Jual Beli Pakaian Bekas Dengan Sistem Karungan Di Pasar Panorama Kota Bengkulu - Trimal Jummarta Erlan; Badarudin Nurhab; Miti Yarmunida (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to find out how the practice of buying and selling used clothes with the sack system in the panorama market and to find out how Islamic business ethics reviews the buying and selling of used clothes with the sack system in the Panorama market of Bengkulu City. This study uses qualitative research methods with data collection techniques through observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of this study indicate that (1)Traders get used clothes from agents in Palembang City with a sack system in the form of a code based on the type of clothing purchased, traders buy used clothes by coming to Palembang but there are also those who buy via telephone and the goods are delivered by the agent. or courier. (2)Judging from the Islamic business ethics of buying and selling used clothes with this sack system, there are still some frauds and ambiguities(gharar) in the object of buying and selling regarding the quality and quantity of the used clothes, and this buying and selling is not in accordance with the principles of business ethics. Islam is unity (Tawhid), balance, truth (Ihsan), responsibility (Responsibility). Keywords: Buying and Selling Used Clothes, Islamic Business Ethics